Effect of Graphene Oxide on UV-Thermo-Humidity Degradation of Environmentally Friendly Alkyd Composite Coating - Nguyen Trung Thanh (Malaysian Journal on Composites Science and Manufacturing, 2022)
This article presents the degradation of environmentally friendly alkyd composite coating containing GO as an anti-UV additive under UV-thermo-humidity conditions. The coatings were exposed under accelerated weathering treatment for 100 cycles. FT-IR spectroscopy, TGA and SEM were used to assess coatings changes before and after accelerated weathering testing. Results showed that gloss loss, adhesion, flexural strength, impact resistance, and relative hardness of coatings were much improved with 1.2 weight percent (wt. %) of GO. FT-IR spectrums of initial and aged coatings without GO illustrated that the aging process led to the increased intensity of CH2 and C=O (ester) groups. The coating with GO exhibited peaks of CH2, and ester groups had been changed slightly. SEM images indicated that the surface morphology of aged samples changed differently depending on the presence of GO. The surface of aged coating without GO was rougher than that of coating with GO after the aging process. Results also indicated that the presence of GO had enhanced the UV-thermo-humidity durability of environmentally friendly alkyd coating.